O zakazie orzekania rozwodu na żądanie małżonka wyłącznie winnego - Szlęzak, Andrzej (Wydział Prawa i Administracji UAM, 1988)
The article analyses some questions raised by a so-called recrimination clause, i.e. the provision prohibiting to decree divorce on a petition submitted by a spouse who is considered solely guilty of the marital breakdown (Art. 56 § 3 of the Family and Guardianship Code). Special attention has been paid to the notion of "exclusive guilt" and to the meaning of the rule allowing to decree divorce despite the petitioner's sole guilt if the respondent's refusal of consent to divorce is deemed contrary to the principles of social co-existence. The author considers the recrimination clause the relic of the past and postulates to abolish it de lege ferenda.
On the interdiction to decree divorce on the petition of a spouse who is solely guilty of the breakdown of marriage